Inefficient use of competitors' forecasts? - André Reslow (Uppsala University, Department of Economics, 2019)
This paper assesses to what extent forecasters make effcient use of competitors' forecasts. Usinga panel of forecasters, I find that forecasters underuse information from their competitors in their forecasts for current and next year's annual GDP growth and inflation. The results also show that forecasters increase the attention to their competitors as the forecast horizon decreases. In a model of noisy information with fixed target forecasts, I confirm the empirical results of underuse of competitors' information. I also extend the model to include a revision cost and show how this can explain the observed ineffciency and observed horizon dynamics. Using the same model framework, I also rule out overconfidence as the main explanation of the observed behavior.
urn:nbn:se:uu:diva-395740
Keywords: C53; D82; E17; E37; 330; Forecast Behavior; Efficiency; Revision Cost; Forecast Smoothing; Overconfidence